OP0248-PARE Understanding The Importance of A Patient's Role in The Management of Ra: Results from A Patient-Based Survey Developed by The Ra Narrative Global Advisory Panel. (15th July 2016) - Koehn, C.; Dikranian, A.; Maniccia, A.; Bananis, E.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, debilitating disease for which there is no cure. Objectives: To identify and better understand the perspective of patients (pts) regarding pt/healthcare provider (HCP) interactions, RA treatment and RA management, based on results from a pt-based survey developed by the RA NarRAtive global advisory panel. Methods: The RA NarRAtive initiative comprises an advisory panel of 39 RA experts (including rheumatologists and pt advocacy group leaders [many with RA themselves]) from 17 countries. A pt-based survey designed by the working group was fielded online across 13 countries between Sept 2014 and Jan 2015. Results are presented for all respondents who consented to the survey. Results: Total of 3649 pts responded to the survey: mean age 52.8 yrs (SD ±15), 59% female. Median time since diagnosis of RA (pt-reported) was 7 yrs. Only 34% of pts (n=1251) described their current overall health as excellent/good. Respondents represented a wide spectrum of self-reported disease activity from mild (39%) to moderate to severe (30%) to severe (8%). Overall, 93% and 50% of pts were under the care of an HCP or rheumatologist/RA specialist, respectively. In total, 59% (2139) of pts were receiving prescribed RA medication, including pain relievers (70%), disease-modifying antirheumatic drugs (DMARDs) (38%), steroids/corticosteroids (32%), and biologic DMARDs (16%). Of these, 38% were not taking their medication as prescribed. Overall, 78% of pts currently taking RA medication were satisfied with their treatment regimen, however 70% desired fewer medications, 57% were worried their medications would fail and 56% wanted more medication choices. The number or dosing frequency of medications was the most frequently cited aspect that pts would most like to change with respect to their current prescribed medications (Figure ). Almost half of pts under HCP care (48%) acknowledged that dialogue with the HCP would optimise management of their RA. However, 62% of respondents felt uncomfortable raising treatment/disease concerns to their HCP. Of those currently seeing an HCP to manage their RA, 34% strongly/somewhat agreed that if they ask too many questions, their HCP will consider them a difficult pt and this may affect the quality of care they receive. The current treatment goal for physicians is to achieve clinical remission or low disease activity. 1 However, successful treatment was most commonly defined by pts as a reduction of pain and/or joint swelling/inflammation (81%) and improvements in quality of life (77%). Conclusions: This pt-based survey highlights the importance of treatment conversations between pts and HCPs. Although many pts are satisfied with their RA treatment, non-adherence persists and many would like to discuss and/or change their currently prescribed treatment. Further understanding the responses from this survey will be important to facilitate communication between pts and HCPs, with the aim of improving treatment outcomes. References: Smolen JS et al. Ann Rheum Dis 2015; 75: 3–15. Acknowledgement: These surveys were funded by Pfizer Inc. Editorial support was provided by S Johnson, PhD, of Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: C. Koehn Shareholder of: Arthritis Consumer Experts, Grant/research support from: Canadian Institutes of Health Research, Arthritis Research Canada, St. Paul's Hospital, Employee of: Arthritis Consumer Experts, A. Dikranian Consultant for: Pfizer Inc, AbbVie, Speakers bureau: Pfizer Inc, AbbVie, A. Maniccia Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc